Analisis Pengukuran Kinerja Rantai Pasok Usaha Pupuk Organik Di PT Isaru Teknologi Nusantara Dengan Pendekatan Supply Chain Operations Reference (SCOR) - Cahyani, Ni Kadek Mira; Dewi, Ida Ayu Listia (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
PT Isaru Teknologi Nusantara is a company engaged in the production of organic fertilizer made from animal manure. PT Isaru experiences uncertainty in the availability of fertilizer stock in the implementation of supply chain management, which can cause the supply chain flow to be less than optimal. This study aims to measure and analyze the supply chain performance of PT Isaru Teknologi Nusantara. Supply chain performance measurement uses a quantitative approach with the Supply Chain Operations Reference (SCOR) model as the performance measurement framework and the Analytical Hierarchy Process (AHP) method for indicator weighting. Based on the identification of key performance indicators (KPIs), there are 24 KPIs that have been validated through the validation process and used in measuring the company's supply chain performance. The final supply chain performance score for PT Isaru was 88,43, falling into the “good” category. The planning process was identified as the top priority for improvement due to its highest weighting of 0.39, yet it had the lowest performance achievement at 87,89%. Out of the 24 indicators that have been measured, there are 5 indicators with low achievement values but high weights, so improvements need to be made to direct improvement priorities more effectively.